Morphological and Morphometrical Study of Dry Fibula at Medical college of Western Nepal - Mukhia, Rajeev; Poudel, Phanindra Prasad; Mansur, Dil Islam; Wahekar, Krishna (Journal of Karnali Academy of Health Sciences, 2022)
Background: The fibula bone that lies lateral to the tibia is important for talocrural joint stabilization. The morphology and morphometry of fibula are important in the design and preparation of fibula flap transfer in mandibular reconstruction. The nutrient foramina location is important for fibular shaft vascularization. Hence, the present study aims to investigate the morphology and morphometry of fibula bone in the Nepalese population.Methods: This study was done on 50 dry fibulas in the Anatomy Department, Manipal College of Medical Sciences, Nepal. With the help of a thread, measuring scale, and vernier caliper the maximum length of fibula, length, and breadth of superior and inferior articulating facets were measured for right and left fibula. The nutrient foramina location on the fibula of both sides was noted. Data collection was analyzed by Microsoft Excel Software 2007 version and reported as mean ± SD.Results: The mean length of right fibula was 33.21±1.42 cm and left fibula was 33.06±1.52 cm. The mean length and breadth of superior and inferior articulating facet was found to be between 1.25 cm to 1.75 cm for the right and left fibula. In middle 1/3rd of the fibula, 77% of nutrient foramina were located, 12.5% were located in upper 1/3rd and 10.41% were located in lower 1/3rd of the fibula. The posterior surface of fibula shows the majority of the nutrient foramina. Conclusion: The Fibula morphology and morphometry is of clinical importance because it will be helpful to surgeons during bone repair, bone grafting, and microvascular bone surgery in Nepalese population.